Evaluation of antibiotic resistance and CTX-M gene in ESBL-producing Escherichia coli by PCR among urine samples of patients reffering to Yahyanejad hospital of Babol city, Iran - Fatemeh Zaboli; Seyed Mojtaba Mahdipour Mir (Jorjani Biomedicine Journal, 2017)
Background and Objectives: Escherichia coli (E.coli) is one of the most common bacteria causing urinary tract infections which has become resistant to beta-lactam antibiotics due to the acquisition of plasmids encoding extended-spectrum beta-lactamases (ESBL). Here, we investigated the phenotype and genotype of Cefotaxsim-M (CTX-M) gene among ESBL-producing Escherichia coli among urine samples of patients reffering to Yahyanejad hospital of Babol city.